Foreign Experience in Taxation in the System of Financial Support for Small Business Development (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article deals with the foreign experience of small businesses taxation. The simplified taxation system features in foreign countries are investigated. The main directions of tax pressure reduction in order to support small enterprises in different countries are determined.